Elucidating the gut microbiome alterations of tribal community of Arunachal Pradesh: perspectives on their lifestyle or food habits - Parijat Hazarika; Indranil Chattopadhyay; Mika Umpo; Yashmin Choudhury; Indu Sharma (Scientific Reports, 2022)
Abstract Gut microbiota studies of ethnic populations reveal gut microbial biomarkers for therapeutic options and detection of the disease state. The present study aimed to analyze the gut microbiome signatures in thirty individuals from the Adi, Apatani and Nyshi tribes of Arunachal Pradesh (ten in each cohort) by sequencing the V3 and V4 regions of 16S rRNA on the Illumina MiSeq Platform. The gut microbiome was highly predominated by Firmicutes, Actinobacteria, Proteobacteria, and Bacteroidates in the three studied tribal groups. At the genus level, significant abundance of Bifidobacterium, Collinsella, Bacteroides, Prevotella, Lactobacillus, Streptococcus, Clostridium, Coprococcus, Dorea, Lachnospira, Roseburia, Ruminococcus, Faecalibacterium, Catenibacterium, Eubacterium, Citrobacter and Enterobacter were observed amongst the three tribes. The tribal communities residing in remote areas and following traditional lifestyle had higher gut microbiome diversity with a high prevalence of Prevotella and Collinsella in the Adi and Nyshi tribes, and Bifidobacterium and Catenibacterium in the Apatani tribe. Elucidating the gut microbiome of the tribal community of Arunachal Pradesh will add to the knowledge on relationships between microbial communities, dietary food factors, and the overall state of health of humans worldwide.